Athletes’ Knowledge of Injury and Management A Survey of Ngawi FC Liga 4 Football Team - Setiawan, Ardhian Dwi; Utomo, Andy Widhya Bayu; Mashuri, Anwas (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to describe and understand Ngawi FC athletes’ level of knowledge regarding injury and its management in the context of Liga 4 football. Utilizing a qualitative approach with a phenomenological method, the study involved eight athletes with previous injury experiences. Data were collected through in-depth interviews, non-participant observation, and documentation, and analyzed using the Miles, Huberman, and Saldaña model. The results revealed that athletes’ knowledge is limited, primarily based on personal experience and lacks systematic education. Not all athletes understood the RICE principle and often relied on intuition and traditional treatments. These findings underscore the need for integrating injury education programs into amateur athlete development, first aid training for coaches, and basic medical facilities at the club level. Sports health education is expected to become an integral component in the structure of athlete development at the regional level.